Influence of temperature and concentration on thermophysical properties of yellow mombin (Spondias mombin, L.) - Assis, Mitzi Maria Martins; Caetano Da Silva Lannes, Suzana; Cecilia Tadini, Carmen; Regina Nicoletti Telis, Vania [UNESP]; Telis-Romero, Javier [UNESP] (Springer Nature, 2006)
Thermal conductivity, thermal diffusivity, and density of yellow mombin juice were determined at 8.8-49.4 °Brix and at temperature from 0.4 to 77.1 °C. Apparent viscosity was also measured between 7.8 and 30 °Brix and at temperature from 0 to 60 °C. Yellow mombin juice was produced from fruits of two different batches and the concentration process was performed using a roto evaporator or a rising film evaporator, single effect, with recirculation, under vacuum, to obtain concentrated juice. In order to obtain different concentrations, concentrated juice was diluted with distilled water. Multiple regression analysis was performed to fit thermal conductivity, thermal diffusivity and density experimental data obtaining a good fit. Arrhenius and power law relationships were proposed to fit apparent viscosity as a function of temperature and juice concentration at typical shear rates found during processing. The rheological parameters together with experimental values of pressure loss in tube flow were used to calculate friction factors, which were compared to those resulting from theoretical equation.
Keywords: Apparent viscosity; Density; Friction factors; Rheology; Thermal conductivity; Thermal diffusivity; Yellow mombin; Spondias mombin